Association of progressive thoracic aortic calcification with future cardiovascular events and all-cause mortality: ability to improve risk prediction? Results of the Heinz Nixdorf Recall (HNR) study. (1st December 2018) - Kälsch, Hagen; Mahabadi, Amir A; Moebus, Susanne; Reinsch, Nico; Budde, Thomas; Hoffmann, Barbara; Stang, Andreas; Jöckel, Karl-Heinz; Erbel, Raimund; Lehmann, Nils
Abstract: Aims: Thoracic aortic calcification (TAC) is measured by computed tomography (CT). We investigated the association of TAC-progression with incident cardiovascular (CV) events and all-cause mortality in a population-based cohort and to determine its predictive value for these endpoints. Methods and results: In 3080 participants (45–74 years, 53.6% women), risk factors and TAC via CT were measured at baseline and at a second examination after 5.1 ± 0.3 years. Hard coronary, hard CV events as well as CV events including revascularization and all-cause mortality were recorded during a follow-up time of 7.8 ± 2.2 years after the second CT scan. Cox regression analysis determined the association of TAC-progression with observed endpoints. The predictive value of TAC-progression was assessed using Harrell's C index. We observed 81 hard coronary, 154 hard CV, 231 CV events including revascularization, and 266 deaths. In the crude analysis, event rates increased continuously with the level of TAC-change over 5 years for all endpoints. After adjustment, the significant association of TAC-progression with hard CV events [hazard ratio (HR) 1.28, 95% confidence interval (CI) 1.05–1.57] and all-cause mortality (HR 1.34, 95% CI 1.14–1.58) persisted, per one standard deviation increase in TAC-progression (log(TAC + 1)). Regarding aortic segments separately, HRs were consistently higher for descending thoracic aorta. When adding TAC (baseline and progression) to the model containing classical risk factors and coronary artery calcification (CAC), Harrell's C indices did not increase for any of the observed endpoints. Conclusion: TAC-progression is associated with incident hard CV events and all-cause mortality but fails to improve event prediction over CAC.